2019
DOI: 10.1161/strokeaha.118.022863
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Early Mortality of Acute Ischemic Stroke

Abstract: Background and Purpose— Several risk factors are known to increase mid- and long-term mortality of ischemic stroke patients. Information on predictors of early stroke mortality is scarce but often requested in clinical practice. We therefore aimed to develop a rapidly applicable tool for predicting early mortality at the stroke unit. Methods— We used data from the nationwide Austrian Stroke Unit Registry and multivariate regularized logistic regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
77
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(85 citation statements)
references
References 31 publications
6
77
1
1
Order By: Relevance
“…The early mortality in our study (31.1%) was similar to those observed in African context, in Ghana (32.7%) [16]. In contrast, the 7-day mortality was lower in western countries where stroke unit is available (2%) [17]. The majority of stroke mortality (79.7%) occurred in the first 7 days, in line with Heuschman et al (66%) [18] but in contrast with Das et al who had found that 50% of case fatality occurred in 7-14 days [19].…”
Section: Discussionsupporting
confidence: 86%
“…The early mortality in our study (31.1%) was similar to those observed in African context, in Ghana (32.7%) [16]. In contrast, the 7-day mortality was lower in western countries where stroke unit is available (2%) [17]. The majority of stroke mortality (79.7%) occurred in the first 7 days, in line with Heuschman et al (66%) [18] but in contrast with Das et al who had found that 50% of case fatality occurred in 7-14 days [19].…”
Section: Discussionsupporting
confidence: 86%
“…The strength of our finding lies in the larger sample size and adjustment for some potential confounders validating the safety of APT prior to EVT, and previous research studies demonstrated that potential confounders such as, age, vascular risk factors (diabetes mellitus and atrial fibrillation), IVT and intra-arterial thrombolysis are predictors for the increase risk of sICH. [22][23][24][25] There has been limited evidence for the effects of oral APT preceding EVT on the clinical outcomes. Previous studies showed that APT did not improve Open access Open access patient's clinical outcomes or reduce the risk mortality at 3-month follow-up although recanalisation could be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…There are many factors that affect in-hospital mortality in patients with acute ischemic stroke (AIS) [1]. These include the patient's age and severity of AIS, which are the strongest determinants of prognosis in the acute phase of stroke [2].…”
Section: Introductionmentioning
confidence: 99%